Novel TMS for Stroke and Depression (NoTSAD): Accelerated Repetitive Transcranial Magnetic Stimulation as a Safe and Effective Treatment for Post-stroke Depression - Frey, Jessica; Najib, Umer; Lilly, Christa; Adcock, Amelia (Frontiers in Neurology, 2020)
Background: Post stroke depression (PSD) affects up to 50% of stroke survivors, reducing quality of life and increasing adverse outcomes. Conventional therapies to treat PSD may not be effective for some patients. Repetitive transcranial magnetic stimulation (rTMS) is well established as an effective treatment for Major Depressive Disorder (MDD) and some small trials have shown that rTMS may be effective for chronic PSD; however, no trials have evaluated an accelerated rTMS protocol in a subacute stroke population. We hypothesized that an accelerated rTMS protocol will be a safe and viable option to treat PSD symptoms. Methods: Patients (N = 6) with radiographic evidence of ischemic stroke within the last 2 weeks to 6 months with Hamilton Depression Rating Scale (HAMD-17) scores greater than 7 were recruited for an open label study using an accelerated rTMS protocol as follows: High-frequency (20-Hz) rTMS at 110% resting motor threshold (RMT) was applied to the left dorsolateral prefrontal cortex (DLPFC) during 5 sessions per day over 4 consecutive days for a total of 20 sessions. Safety assessment and adverse events were documented based on the patients’ responses following each day of stimulation. Before and after the 4-day neurostimulation protocol, outcome measures were obtained for the HAMD, modified Rankin Scale (mRS), functional independence measures (FIM), and National Institutes of Health Stroke Scales (NIHSS). These same measures were obtained at 3-month follow up. Results: HAMD significantly decreased (Wilcoxon p = 0.03) from M=15.5 (2.81) to 4.17 (0.98) following rTMS, a difference which persisted at the 3-month follow-up (p=0.03). No statistically significant difference in FIM, mRS, or NIHSS were observed. No significant adverse events related to the treatment were observed and patients tolerated the stimulation protocol well overall. Conclusions: This pilot study indicates that an accelerated rTMS protocol is a safe and viable option, and may be an effective alternative or adjunctive therapy for patients suffering from PSD. Future randomized, controlled studies are needed to confirm these preliminary findings. Clinical Trial Registration: https://clinicaltrials.gov/ct2/show/NCT04093843